Does restriction of glenohumeral horizontal adduction reflect posterior capsule thickening of the throwing shoulder? - Ishigaki, Tomonobu (J Phys Ther Sci, 2015)
[Purpose] Glenohumeral posterior capsule tightness possibly relates to posterior capsule thickness (PCT). The purpose of the current study was to analyze the relationships between PCT and glenohumeral range of motion (ROM) in horizontal adduction (HAdd) and internal rotation (IR). [Subjects and Methods] This study recruited 39 healthy collegiate baseball players. We measured PCT by using ultrasonography and ROM of the glenohumeral joint of the throwing shoulder by using a digital inclinometer. Pearson’s correlation coefficients were calculated between PCT and HAdd or IR ROM. [Results] There was no correlation between PCT and HAdd ROM, but PCT was significantly correlated with IR ROM. [Conclusion] This result indicates that posterior shoulder capsule tightness only relates to IR ROM, and that restricted HAdd ROM might reflect tightness of other tissue, such as the posterior deltoid.